2015
DOI: 10.1021/acs.langmuir.5b00854
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Tailored Colloidal Molecules Obtained by Self-Assembly of Model Gold Nanoparticles with Flexible Polyelectrolyte

Abstract: ABSTRACT.We study the effect of citrate to gold molar ratio (X) on the size of citrated gold nanoparticles (AuNPs). This dependence is still a matter of debate for X  3 where the polydispersity is yet minimized. Indeed, there is no consensus between experiments proposed so far for comparable experimental conditions. Nonetheless, the sole available theoretical prediction has never been validated experimentally in this range of X. We show unambiguously using 3 techniques (UV-Vis spectroscopy, dynamic light scat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 80 publications
3
32
0
Order By: Relevance
“…1 Indeed, it has been shown that the electrostatic complexation of cationic gold NPs (AuNPs) with DNA enables to assemble a finite number of NPs in stable linear nanostructures in water by simple mixing. 14 Similar results were then reported with silica NPs 15 and other polyelectrolytes such as chitosan, 16,17 hyaluronic acid, 18,19 polystyrene sulfonate 20 and polylysine. 18 However, as shown theoretically 21 and experimentally 18 , the interparticle distance within these assemblies is governed by the electrostatic interactions.…”
Section: Introductionsupporting
confidence: 80%
“…1 Indeed, it has been shown that the electrostatic complexation of cationic gold NPs (AuNPs) with DNA enables to assemble a finite number of NPs in stable linear nanostructures in water by simple mixing. 14 Similar results were then reported with silica NPs 15 and other polyelectrolytes such as chitosan, 16,17 hyaluronic acid, 18,19 polystyrene sulfonate 20 and polylysine. 18 However, as shown theoretically 21 and experimentally 18 , the interparticle distance within these assemblies is governed by the electrostatic interactions.…”
Section: Introductionsupporting
confidence: 80%
“…The past decade has witnessed great progress in NP self-assembly, yet the quantitative prediction of the architecture of NP ensembles remains a challenge. Hierarchical organizations can be triggered in solution by various mechanisms, such as van der Waals attraction [8], polymerization of functionalized NPs [9,10], lock-and-key binding, depletion [11], magnetic field [12], and electrostaticinteractions [13][14][15] to initiate the self-assembly from the NP level to the mesoscopic one.Among them, the association of charged NPs induced by complexation with (bio)polyelectrolytes (PELs) of opposite charge is a simple fast, robust, cost-efficient (bio)-process that can lead to new nano-objects, also called electrostatic complexes.In spite of this large interest, none systematic work has been undergone considering a quite simple aspect as far as chains are concerned: the effect of rigidity of the chain, namely its persistence length, which in a sensible approach, can be compared with the NP size. First approaches have been published: in a preliminary communication [13], we described the complexation between model negatively charged spherical silica NPs with radius R~10 nm and chitosan, a natural polyelectrolyte bearing positive charges with a semi-rigid backbone characterized by an intrinsic persistence length of L p~9 nm, using a combination of cryo-TEM, light, small-angle neutron and X-rays scattering.…”
mentioning
confidence: 99%
“…15,16 Mesoscale assemblies of polyelectrolytes (PEs) and nanocolloids (nanoparticles [NPs], proteins, macroions) into micellar [17][18][19][20] and rodlike [21][22][23] structures have been reported 24 alongside demonstrations of close-packed assembly of charged NPs using PEs. [25][26][27][28][29][30] Such approaches provide an alternative route to create supramolecular NP assemblies that are typically created via DNA grafting-mediated self-assembly, [31][32][33][34][35][36] lithography, [37][38][39][40] and evaporation-based assembly [40][41][42][43] which lack scalability and have high costs associated with their production. 40 Use of PEs to create NP assemblies can potentially overcome these limitations and provide a cost-effective alternative for the bulk production of such architectures.…”
Section: Introductionmentioning
confidence: 99%
“…Electrostatic interaction‐driven self‐assembly of charge‐bearing macromolecules and nanocolloids has garnered recent attention owing to their applications in diverse areas such as protein encapsulation, 1,2 delivery 1,3 and purification, 4–6 diagnostics, 7 biosensing, 8–10 water treatment, 11,12 catalysis 13,14 and mesoporous zeolite synthesis 15,16 . Mesoscale assemblies of polyelectrolytes (PEs) and nanocolloids (nanoparticles [NPs], proteins, macroions) into micellar 17–20 and rod‐like 21–23 structures have been reported 24 alongside demonstrations of close‐packed assembly of charged NPs using PEs 25–30 . Such approaches provide an alternative route to create supramolecular NP assemblies that are typically created via DNA grafting‐mediated self‐assembly, 31–36 lithography, 37–40 and evaporation‐based assembly 40–43 which lack scalability and have high costs associated with their production 40 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation